(untitled) (Revista Contexto & Saúde, 2020)
Objective: to assess the nutritional status and food intake of institutionalized elderly, verifying possible relationships between them. Methodology: it was a cross-sectional descriptive study with a quantitative approach, involving 48 elderlies. Weight (W), height (H), body mass index (BMI), arm circumferences (AC), calf (CC) and waist (WC), triceps skinfold (TSF), and arm muscle circumference were evaluated (AMC). The three-day 24h food record (R24h) was used to analyze food consumption. Spearman’s correlation was applied to verify the relationship between anthropometry and food consumption. Results: it was found that the majority of the elderly were overweight, abdominal adiposity and malnutrition according to the assessment of AC and AMC. CC was within the normal range, and TSF indicated obesity only among men. Insufficient consumption of fibers, calcium, vitamins D and E was found, while saturated fat, iron and proteins (g/kg) were above the recommendation in both sexes. There was a weak correlation between anthropometric variables and total calories, macronutrients and fibers. Conclusion: it was possible to confirm the nutritional status of institutionalized elderly, marked by the coexistent excess weight with muscle loss, and it was concluded that this is related to the distribution of macronutrients, especially with regard to the percentage of lipids and carbohydrates. It is suggested that this condition is aggravated by the sedentary lifestyle of the elderly, since the increased consumption of proteins did not prevent the loss of muscle mass.